THE USE OF VIDEOS TO IMPROVE STUDENTS' SPEAKING ABILITY: A Quasi-Experimental Study to the Seventh Grade Students of Junior High School in Bandung) - S. R., Shinta Puspita (2013)
This study is a quasi-experimental study which examines the effectiveness of video use in teaching learning process to improve students' speaking ability. In addition, it tries to find out students' responses toward the use of video in teaching learning speaking. The study was conducted at one of Junior High School in Bandung with 78 sample students of seventh graders. The study employed a non-equivalent control group design, both experimental and control groups were given pretest and post test after the experimental group was treated by using video technique proposes by Baxter (1994), Stempleski (1990, cited in Richard and Renandya, 2007), Stempleski and Tomalin (2010) for six meetings. The data obtained from pretest and posttest then were analyzed using t-test SPSS version 17.0. The findings indicated that the use of video was effective in improving students' speaking ability. In addition, the questionnaire was only given to the experimental group. The questionnaire consisted 12 closed-ended questions. They were analized by percentage based on Ningrat (2000, cited in Mulyadin, 2003). The findings revealed that most of students gave positive responses since video could help them in their learning process. As the result, students' participation arose and their speaking ability improved. In reference to the result of this study, it can be conclude that the use of video is recommended to be applied in teaching learning speaking to the junior high school students. Moreover, the teachers who are interested in carry out the video in teaching learning speaking need to have well preparation such as checking the equipment, organizing the class, and arranging good lesson plan. Key words: videos, speaking ability Penelitian ini adalah penelitian kuasi eksperimental yang menguji keefektifan dari penggunaan video dalam proses belajar mengajar untuk meningkatkan kemampuan speaking siswa. Lebih lanjut lagi, penelitian ini mencoba mencari tau respon siswa terhadap pengguanaan video dalam proses belajar mengajar speaking. Penelitian ini dilakukan di sebuah sekolah menengah pertama di bandung dengan menggunakan 78 siswa kelas tujuh sebagai sampel penelitian. Penelitian ini menggunakan sebuah desain non-ekuivalen grup kontrol, dimana grup eksperimantal dan grup kontrol diberikan pretest dan posttest setelah grup ekperimental mendapatkan perlakuan (treatment) menggunakan teknik video yang digagas oleh Baxter (1994), ), Stempleski (1990, tercantum di Richard and Renandya, 2007), Stempleski and Tomalin (2010) selama enam pertemuan. Data yang diperoleh melalui pretest dan posttest kemudian dianalisis menggunakan t-test SPSS versi 17.0. Hasil penemuan mengindikasikan bahwa pengguanaan video terbukti efektif dalam meningkatkan kemampuan speaking siswa. Lebih lanjut lagi, grup eksperimental diberikan kuisioner. Kuisioner tersebut terdiri dari 12 pertanyaan tertutup yang kemudian dianalisis menggunakan persentase yang digagas oleh Ningrat (2000, tercantum di Mulyadin, 2003). Hasil penemuan dari kuisioner menunjukkan bahwa sebagian besar siswa memberikan respon positif dikarenakan video dapat membantu mereka dalam proses belajar. Sehingga, partisipasi siswa meningkat begitu pula dengan kemampuan speaking mereka. Dengan mengacu kepada hasil dari penelitian ini, maka dapat disimpulkan bahwa penggunaan video dianjurkan untuk dilakukan dalam proses belajar mengajar speaking kepada siswa sekolah menengah pertama. Tambahan lagi, untuk guru yang tertarik menggunakan video dalam proses belajar mengajar speaking perlu melakukan persiapan yang baik seperti mengecek peralatan, mengatur kelas, dan menyusun RPP yang baik. Kata kunci: video, kemampuan speaking